A „nagy háború” hatása a magyar felsőoktatásra és az egyetemi ifjúságra - Kerepeszki, Róbert (Gerundium, 2019)
The ’Great War’s Influence on the Hungarian Higher Education and Youth. The study examines the different effects that occurred as a consequence of the First World War, such as the reduction of student numbers due to enlisting the army, the society’s reaction to the increased number of women and Jewish students, the reduced activity of university societies, the loss of territory due to war, the continuous inflation, and the radical right wing’s reaction to the lack of stability of the Hungarian youth. These consequences resulted in the increased popularity of the so called association of army brotherhood. To sum up, the author concludes that the Hungarian higher education wasn’t well prepared for the war, which in turn resulted in a number of negative consequences in the following decades.